Institutional pressures, environmental management practices, firm characteristics and environmental performance - Bananuka, Juma; Bakalikwira, Lasuli; Nuwagaba, Patience; Tumwebaze, Zainabu (Accounting Research Journal, 2021)
The purpose of this paper is twofold: to establish the contribution of institutional pressures, environmental management practices and firm characteristics to environmental performance; and to establish whether environmental management practices mediate the relationship between institutional pressures and environmental performance. Design/methodology/approach – Using a cross-sectional design, data were collected through a questionnaire survey of 303 manufacturing firms in Uganda. Data were analyzed using Statistical Package for Social Sciences and MedGraph program (Excel version). Findings – Both environmental management practices and institutional pressures are significant predictors of environmental performance. Results further suggest that environmental management practices partially mediate the relationship between institutional pressures and environmental performance. Variables that represent firm characteristics are not significantly associated with environmental performance. Originality/value – This study provides an initial empirical evidence on the mediating role of environmental management practices in the relationship between institutional pressures and environmental performance. It also enhances our understanding of the contribution of individual dimensions of environmental management practices and institutional pressures to environmental performance using evidence from an emerging economy setting.
Keywords: Environmental performance; Institutional pressures; Environmental Management Practices; Manufacturing firms; Institutional theory; Stakeholder theory